Direct Evidence for Dextral Shearing in the Shanxi Graben System: Geologic and Geomorphologic Constraints From the North Liulengshan Fault. Issue 12 (29th November 2022) - Luo, Quanxing; Li, Youli; Schoenbohm, Lindsay; Rimando, Jeremy; Hu, Xiu; Guo, Ailun; Zhao, Junxiang; Li, Xinnan; Liu, Qingri; Jiang, Shanru; Li, Chuanyou; Sun, Kai
Abstract: The Shanxi Graben System (SGS) is one of the first‐order Cenozoic tectonic features in North China. Understanding the kinematics of this tectonic system is crucial for deciphering the mechanism of continental rifting and the deformation pattern across North China. Although the SGS has long been thought to be a right‐lateral, transtensional shear zone, the geologic and geomorphologic evidence for dextral strike‐slip along its internal faults was slim and even controversial. Field investigations, interpretations of satellite imagery, and construction of decimeter‐scale digital elevation models from unmanned aerial vehicle surveys were used in this work to investigate the tectonic geomorphology of the eastern segment of the North Liulengshan Fault (NLSF) in the northern SGS. Although this fault segment was previously thought to be a pure normal fault, the presence of geomorphic features such as right‐laterally offset terrace risers and gullies, along with an analysis of fault‐slip data, suggests a component of right‐lateral strike‐slip displacement. Combined with optically stimulated luminescence dating of offset fluvial terraces, the late Quaternary right‐lateral strike‐slip and vertical slip rates of this fault segment are both estimated to be ∼0.2–0.3 mm/yr. The discovery of dextral strike‐slip along the NLSF provides compelling direct evidence for determining the dextral transtensional kinematics of the SGS. This puts new constraints on our knowledge that the evolution of the SGS is primarily driven by the outward expansion and growth of the Tibetan Plateau and supports the "bookshelf" rotation kinematic model for North China. Plain Language Summary: It has long been believed that many right‐lateral strike‐slip faults may exist in the Shanxi Graben System (SGS) in central North China, but exactly which ones are not fully understood. Here, we report on a newly discovered dextral strike‐slip fault—the North Liulengshan Fault in the northern SGS, based on interpretations of historical satellite images and field investigations. The dextral strike‐slip motion along the eastern segment of that fault is evidenced by geomorphic features like right‐laterally offset terrace risers and gullies and fault striations preserved on exposed fault planes. Combining our displacement measurements and geochronology data yields both right‐lateral strike‐slip and vertical slip rates of ∼0.2–0.3 mm/yr for the fault. This discovery provides key geologic and geomorphic evidence for determining the kinematics of the SGS, which is of great significance for better understanding the geodynamics of the SGS and the deformation pattern of North China. Key Points: We present direct and compelling evidence for the dextral shearing of the Shanxi Graben System Dextral strike‐slip along the eastern segment of the North Liulengshan Fault (NLSF) is significant in addition to normal faulting Late Quaternary dextral strike‐slip and vertical slip rates along the eastern segment of the NLSF are both ∼0.2–0.3 mm/yr